2020
DOI: 10.7150/jca.44494
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors among Brain Metastases in Newly Diagnosed Ovary Cancer: A Large Real-world Study

Abstract: Background: Population-based data on the prognosis of brain metastases at initial diagnosis of ovary cancer (OCBM) are currently lacking. Besides, the effective treatment for OCBM patients is still controversial now. The study aimed to explore the prognostic factors among OCBM. Methods: We retrospectively reviewed the OCBM patients from the Surveillance, Epidemiology, and End Result (SEER) database of the National Cancer Institute to investigate predictors of the presence of OCBM and its' prognostic factors re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(57 reference statements)
1
4
0
Order By: Relevance
“…There was difference in survival among ovarian cancer patients with different CNS metastatic timing. In our study, patients with CNS metastases in first relapse had better survival outcomes compared with those with CNS metastases in late relapse, while patients with brain metastases at initial diagnosis of ovarian cancer had very poor outcomes with median survival of 2 months (43). Like our results, Xi et al found that survivals of patients with brain metastases in newly diagnosed ovarian cancer can benefit from combined treatment (43).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…There was difference in survival among ovarian cancer patients with different CNS metastatic timing. In our study, patients with CNS metastases in first relapse had better survival outcomes compared with those with CNS metastases in late relapse, while patients with brain metastases at initial diagnosis of ovarian cancer had very poor outcomes with median survival of 2 months (43). Like our results, Xi et al found that survivals of patients with brain metastases in newly diagnosed ovarian cancer can benefit from combined treatment (43).…”
Section: Discussionsupporting
confidence: 74%
“…However, we observed that one-third of patients in our study developed CNS metastatic tumors during the first episode of recurrence. A large population-based study also found 0.3% of patients with newly diagnosed ovarian cancers already had brain metastases (43). There was difference in survival among ovarian cancer patients with different CNS metastatic timing.…”
Section: Discussionmentioning
confidence: 94%
“…This supports the hypothesis that brain mets can be established early during the course of disease but may take a long period of time to adapt to the brain microenvironment and progress to cause symptoms. This hypothesis is also supported by the clinical impression that brain mets have become slightly more frequent with the improvement in the systemic treatment of EOC ( 2 7 ) and the increase in overall survival. Thus, confirming this hypothesis in a larger cohort of patients with EOC brain mets will be critical to identify and implement effective prevention and therapeutic strategies against EOC brain mets.…”
Section: Discussionmentioning
confidence: 71%
“…The incidence of brain metastases (brain mets) in epithelial ovarian cancer (EOC) patients is about 2%–6% and invariably results in death ( 1 ). This represents a clinical challenge, since there are currently no established guidelines for the detection and treatment of this severe and irreversible condition ( 2 7 ). Previous studies in EOC have shown that brain mets display a unique phenotype and do not respond to systemic therapy in the same way as extracranial tumors ( 1 , 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regrettably, the tool quantifying risk of LM development is not available. Earlier studies focusing on OC with bone and brain metastases suggested that advanced T stage, N stage, tumor grade, and metastases to other distant organs were predictive factors for bone and brain metastases 9 , 24 . Previous population-based studies determined older age, race, unmarried status, bilateral tumor location, non-serous histology, advanced T and N stages, grades, and elevated CA-125 were risks for liver metastases 5 , 7 , our study supported this association.…”
Section: Discussionmentioning
confidence: 99%